2016
DOI: 10.3889/oamjms.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Corridors: A Fact or a Myth in the Eyes of Laymen?

Abstract: AIM:This study aimed to investigate laymen knowledge of the existence of the buccal corridor and whether it was an important factor for them in judging smile attractiveness and the effect of introducing the knowledge to them on their further judgment.MATERIALS AND METHODS:Nine subjects were randomly selected with variable buccal corridor percentages. They were coached to smile in a posed fashion and full face smile photographs were taken from a standardised distance. The photographs were randomly arranged in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The corridors found in this study were smaller. However, it should be noted that different studies have found that buccal corridors do not significantly affect smile aesthetics [ 6 , 8 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The corridors found in this study were smaller. However, it should be noted that different studies have found that buccal corridors do not significantly affect smile aesthetics [ 6 , 8 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%